Do We Need Natural Language? Exploring Restricted Language Interfaces for Complex Domains - Mu, Jesse; Sarkar, Advait (37th Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems (CHI '19 Extended Abstracts), 2019)
Natural language interfaces (NLIs) that aim to understand arbitrary language are not only difficult to engineer; they can also create unrealistic expectations of the capabilities of the system, resulting in user confusion and disappointment. We use an interactive language learning game in a 3D blocks world to examine whether limiting a user’s communication to a small set of artificial utterances is an acceptable alternative to the much harder task of accepting unrestricted language. We find that such a restricted language interface provides same or better performance on this task while improving user experience indices. This suggests that some NLIs can restrict user languages without sacrificing user experience and highlights the importance of conveying NLI limitations to users.